Cyberbullying and Internet Crimes: Aspects of Victims and Offenders with Mental Disorders - Liana Spytska (Revista de Direito, Estado e Telecomunicações)
[Purpose] Cyber aggression is a phenomenon that has roots in most Internet and social media users. People with psychiatric disorders have impaired self-regulation and exacerbation of many character traits, which makes them a high-risk group for the negative effects of cyberbullying. However, the scientific literature does not pay enough attention to the psychological aspects of the impact of cyberbullying on people with mental disorders. The study aims to address the characteristics of victims and perpetrators of cyberbullying with psychiatric disorders.[Methodology/approach/design]The study involved 60 patients with mild to moderate psychiatric diagnoses. Among them, there are 15 patients with diagnoses: of depressive disorder, anxiety disorder, bipolar disorder, and personality disorder. The analysis was carried out using self-report methods and studied indicators of involvement in cyberbullying and online aggression, personality traits and negative traits that make up the dark triad, as well as the level of life satisfaction.[Findings]The study determined that the level of involvement in cyberbullying in the study sample was quite high, amounting to 34%, of which 40% were victims and 28% were aggressors. The correlation analysis showed a high positive correlation between cyber victimization and indicators of openness to new experiences and a negative correlation with the stability indicator. Cyber victimization was also negatively correlated with the dark triad traits: psychopathy, Machiavellianism and narcissism. Cyberaggression was positively correlated with extraversion and negatively correlated with friendliness and conscientiousness. The strongest positive statistical correlation was found with the Dark Triad indicators, most notably with psychopathy, and the weakest with narcissism and Machiavellianism. These results are consistent with the data described in the literature on non-clinical samples. Both components of cyber-aggressive behavior were negatively correlated with life satisfaction. [Practical implications]The results provide insight into the psychological characteristics of cyber criminals and their victims in a sample with mental disorders.